Adaptation of Childhood Emotional Abuse Measurement Instrumen in Indonesia - Sari, Meita (COUNS-EDU: The International Journal of Counseling and Education, 2024)
Childhood emotional abuse has long-term impacts on individuals. A specific measuring instrument to measure the history of childhood emotional abuse in Indonesian adolescents is needed. The current study adapted the Emotional Abuse Questionnaire developed by Momtaz et al. (2022) into an Indonesian version (ID-EAQ). Participants in this study were 100 adolescents aged 17-21 years, selected using a purposive sampling technique. The adaptation was carried out with the guidance of the International Test Commission (2016). The results showed that the ID-EAQ has a high level of validity and reliability with a value of 0.921. It can be concluded that the ID-EAQ is a valid and reliable measuring instrument to measure the history of childhood emotional abuse in adolescent samples